Jadwal Kegiatan pada Sekolah Sehari Penuh dalam Menanamkan Kedisiplinan - Zyaqiah Almuna Wara; Serli Marlina (Universitas Trunojoyo Madura, 2019)
This study aims to describe about the application activity schedule of full day school in Primagama Creative Kindegarten Padang. This study used a descriptive method with a qualitative approach. Informants from this study were principal and full day teachers. The techniques of data collection in this study were observation technique, interview technique, and documentation technique. The data analysis techniqueused was data triangulation technique. The results of the study were generally known that the application of activity schedule of dull day school in instilling disciplinary in Primagama Creative Kindegarten Padang have been well implemented. The teachers have made planning, implementation, and evaluation that was able to develop children’s discipline attitudes through habituation with scheduled activities. So, it can be concluded that planning, implementation, and evaluation carried out in order to instill a discipline in children was accordance with the guidelines designed by the teachers.